Improving entity relationship modeling accuracy with novice data modelers - Bock, Douglas B; Yager, Susan E (The Journal of computer information systems, 2001)
One of the most remarkable improvements for the WITH group was in modeling both of the ternary relationships. The WT group was about four to six times more successful in modeling ternary relationships than the WITHOUT group. The most common WIHOUT group mistake was modeling the ternary relationships as a series of connected binary relationships.